Condiciones climáticas, vegetación, densidad y estructura etaria de Ranitomeya reticulata Boulenger 1883 (anura: Dendrobatidae) en el bosque de Varillal del CIEFOR, Iquitos-Perú - Taricuarima Pérez, Heisen Hernando (2023)
From February to May 2022, in the varillal forest of the CIEFOR was evaluated climatics conditions, vegetation, density and age structure of Ranitomeya reticulata (ANURA: DENDROBATIDAE) by direct observation.The results indicate that the temperature of the undergrowth of the CIEFOR varillal forest during the day varied from 24 to 28.82 °C and the relative humidity between 80.6 (16 hours) and 98.6 % (18 hours).The species richness of plants was 217 species, with predminance of Fabaceae, Myristicaceae, Burseraceae, Lauraceae, Euphorbiaceae, Annonaceae, Meliaceae, Sapotaceae, Urticaceae, Apocynaceae, Elaeocarpaceae, Lecythidaceae and Moraceae. Ranitomeya reticulata in the varillal forest of CIEFOR was a bimodal density, with 37.33 ind/km2 in march and 22.50 ind/ km2 in april, and the age structure does not form of the broad-based pyramid. It is concluded that the climatics conditions (precipitation, temperature and relative humedity) in which the specie of Ranitomeya reticulata develops, in the CIEFOR varillal forest, are within the tolerance range favoring their presence in their different stages of development.